Pengaruh Adanya Literasi Digital terhadap Menurunya Sikap Sosial di Lingkungan Masyarakat - Evi Setianingsih; Fani Widia Putri; Tin Rustini; Yona Wahyuningsih (Journal on Education, 2023)
In the millennial era and technological advances as it is today, the use of digital media is increasingly becoming the most important thing. All groups have started using technology, teachers and students are the most active in the use of this digital media. Research on the influence of digital literacy associated with social attitudes tends to be less done. The subject of this research is the community, ranging from teachers, students and even the general public. This study uses a qualitative method with a case study approach. The findings obtained in this study are the influence of digital literacy on social attitudes that arise, whether these social attitudes tend to increase or even have a negative impact, namely they tend to decrease in social attitudes after digital literacy. Therefore, the influence of digital literacy in the community must be considered, so that it can be known whether or not digital literacy affects the decline in social attitudes in the community.